História: - Pereira de Oliveira, João; Corrêa Filho, Virgilio (A Defesa Nacional, 2020)
I - Uma Página da Campanha do Contestado - Gen .João Pereira de Oliveira II - .Pedro Alvares Cabral - . Virgílio Corrêa Filho